Sentiment Analysis, Classification of Twitter Tweets of the Constitutional Court Decision on Vice Presidential Candidates Using Naïve Bayes Method - Nurlita, Nurlita; Rudiman, Rudiman; Hallim, Abd (JSE Journal of Science and Engineering, 2025)
The development of information technology has had a significant impact on the acceleration and ease of exchanging information and communication. The emergence of popular social media platforms, such as Twitter, Facebook, Instagram, Youtube in order to explore trending and popular information. Social media has become a reference for the Indonesian people in considering all possibilities that are happening, including public unrest against decision-making that is not in accordance with the norms and ethics within the scope of the constitutional court. Decisions issued by the Constitutional Court (MK) have the potential to trigger significant reactions and debates in society. In this research, we conducted a sentiment analysis on the current issue of the Constitutional Court, where the problem is that many people doubt the decisions taken and many also support the decision so that the virtual world becomes a place for people to express their thoughts about it, especially on the Twitter platform. In expressing their thoughts on the Twitter platform will display Positive, Negative, and Neutral expressions. The method used to see the results of the analysis of the Constitutional Court Decision is the Naïve Bayes method to get accurate results. By using 540 data, the total data of F1 results is the average of precission and recall: AUC of 93.8%, Classification accuracy (CA) of 21.7% Model accuracy of 97.1% Recall of 21.7% F1 score of 14.8%, with a total of 540 data, a total of 10 negative actual data, while 7 positive and 523 neutral. With these results, many people respond to the results of the Constitutional Court's decision Neutral.